Natural Radionuclides Concentrations and Associated Radiation Hazard of Some Building Rocks Used in Taiz City, Yemen - Mohamed N. Dahesh; Samir Y. El-Kameesy; Mogahed E. Al-Abyad; Gobran N. Ali; Abdullah T. Naji (University of Science and Technology, Sana'a, Yemen, 2023)
Building materials comprise a diverse range of natural rocks that contain varying mineral components including radionuclides. Gamma spectrometry-based high-purity Germanium detectors were utilized to measure the activity concentrations of natural radionuclides: Radium-226 (226Ra), Thorium-232 (232Th), and Potassium-40 (40K) in various building rock samples found within and surrounding Taiz city. The activity concentrations of226Ra,232Th, and40K vary from 27.79 0.77 to 234.49 3.13 Bq.kg-1, 25.82 0.40 to 415.31 2.47 Bq.kg-1, and 457.912.61 to 1139.56 5.43 Bq.kg-1with overall average value of 71.55 Bq.kg-1, 93.87 Bq.kg-1,966.88 Bq.kg-1respectively, these values were higher than the permissible thresholds. Furthermore, several radiation hazard indices were estimated including the radium equivalent (Raeq), the external hazard index (Hex), the internal hazard index (Hin), the gamma level index (I?), the dose rate(D?), the annual effective dose equivalent (AEDE), the excess lifetime cancer risk (ELCR), and the annual gonadal dose equivalent (AGDE). The findings illustrated that Basalt rocks have the minimum values of radiation hazard indices while the Himatite rocks have the maximum values of radiation hazard. The average values of radiation risks for most of building rocks fall below the recommended limits for safety. Based on the Radiation hazard indices of building rock samples, it can be concluded that with the exception of hematite rocks, all the examined rocks are considered safe for use in construction materials and pose non-significant radiation risks. The awareness about natural radioactivity levels of building rocks is critical for planning and performing strategies in radiation safety of buildings.